An Investigation into the Mental Structure of Science Teacher Candidates towards the Concept of “Atom” - Yaşar, Mehmet Diyaddin (Science Insights Education Frontiers, 2024)
This study aimed to identify science teacher candidates’ mental structures about the concept of the atom. This study included 120 science teacher candidates who were chosen using the convenience sampling method. This research is a pheno-menological study. The data on students’ mental models of the atom was collected using a metaphor form and an open-ended question form. Forms were utilized to collect written feedback from teaching candidates. The research data were subjected to content analysis. In addition, the MAXQDA application was utilized to assess and generate categorization. As a result of the research, science teacher candidates’ mental structures about the concept of the atom were divided into six major categories. It has been discovered that atom models are most vividly represented in the mental structures of science teacher candidates while addressing the concept of the atom. Then, mental structures relating to the atom’s structural properties, definition or conceptual explanation, historical process, subatomic particles, and functional function arose in that order. When the codes in these categories were reviewed in detail, it was discovered that the explanations provided were extremely cursory.